A mixed high corrosion-resistant FeSiCr electromagnetic wave absorber and preparation method thereof
By preparing FeSiCr powder into spherical and sheet-like powders and mixing them to form a highly corrosion-resistant FeSiCr electromagnetic wave absorber, the problem of insufficient corrosion resistance in the marine environment in the prior art is solved, and the problem of insufficient corrosion resistance in the marine environment is achieved. The microwave high frequency band has the effects of high magnetic permeability and corrosion resistance.
Patent Information
- Application Number
- CN202211414856.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-11
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2042-11-11
AI Technical Summary
The existing FeSiCr electromagnetic wave absorbers are insufficient in the marine environment, and it is difficult to meet the requirements of corrosion resistance and electromagnetic wave absorption characteristics at the same time.
The FeSiCr powder is prepared into a spherical powder of 2 to 5 μm and a sheet-shaped powder with a particle size <10 μm, and is mixed and mixed to form a mixed type high corrosion-resistant FeSiCr electromagnetic wave absorber. This method can adjust the peak and density of magnetic permeability and is suitable for specific frequency bands in marine environments.
It realizes an electromagnetic wave absorber with high magnetic permeability and corrosion resistance in the high frequency band of microwaves. It is suitable for coating materials in marine environments, and has a simple process, low cost and is easy to industrially apply.
Smart Images

Figure CN116174704B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electromagnetic wave absorbers, and in particular to a mixed high-corrosion-resistant FeSiCr electromagnetic wave absorber and a preparation method thereof. Background Art
[0002] The marine corrosion environment includes the marine atmosphere zone, splash zone, tidal range zone, full immersion zone and sea mud zone. The marine atmosphere has high humidity and contains salt, and its corrosion rate is often 4 to 5 times higher than that of the inland atmosphere. Pipes or facilities in the splash zone are often impacted by waves and floating objects, and the surface is alternately dry and wet. There is sufficient moisture and oxygen supply, which is the most corrosive area in the marine environment. Marine corrosion is mainly local corrosion, that is, corrosion that starts from the surface of the component and occurs in a very small area, such as galvanic corrosion, pitting corrosion, crevice corrosion, etc. The use of thick paste anti-corrosion coatings is the main method to prevent marine corrosion.
[0003] As a traditional soft magnetic material, FeSi metal powder has good electrical conductivity, high Curie temperature and large saturation magnetization. However, in the marine environment, due to the influence of chloride ions, the corrosion resistance of FeSi or FeSiAl alloy is very poor, the corrosion rate reaches about 0.2mm / year, and the corrosion resistance level is 6. Metal Cr can improve the oxidation resistance and corrosion resistance of the alloy and inhibit grain growth. Smaller grain size is conducive to the formation of a continuous protective corrosion product film. Adding a certain amount of Cr to FeSi alloy can optimize the microstructure and improve the magnetic permeability, ductility and corrosion resistance of the material. Therefore, FeSiCr alloy is widely used as a microwave absorbing material in the microwave frequency band. The particle size of the absorbent will affect the peak value of the magnetic permeability, and the iron content will affect the frequency of the peak. Therefore, when designing the absorbent component in the prior art, it is necessary to fully consider that the iron content cannot be less than 88wt%, and the particle size of the absorbent should be about 10μm.
[0004] In the marine environment, metal parts of large ships, aircraft, etc. must take into account both corrosion resistance and electromagnetic wave absorption properties. Therefore, it is urgent to develop anti-corrosion coatings with high corrosion resistance and electromagnetic wave absorbers for both national defense and civilian use.
[0005] The existing technologies related to FeSiCr are almost all focused on the surface coating of powders. For example, patents with publication numbers CN111575603A and CN109054740A are all related to powder preparation and coating, but lack research on the corrosion resistance of FeSiCr powders.
[0006] Therefore, a hybrid high corrosion-resistant FeSiCr electromagnetic wave absorber and a preparation method thereof are proposed. The hybrid high corrosion-resistant FeSiCr electromagnetic wave absorber prepared by the method has strong electromagnetic wave absorption performance in the microwave high frequency band and strong corrosion resistance. The method can simultaneously adjust the peak value and density of the magnetic permeability of the electromagnetic wave absorber, thereby meeting the use requirements of a certain specific frequency band. Summary of the invention
[0007] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a hybrid high corrosion resistant FeSiCr electromagnetic wave absorber and a preparation method thereof. The hybrid high corrosion resistant FeSiCr electromagnetic wave absorber has the characteristics of strong high frequency absorption capacity and high corrosion resistance, and the method can simultaneously adjust the peak value and density of the magnetic permeability of the electromagnetic wave absorber, thereby achieving the use requirements of a certain specific frequency band.
[0008] The objective of the present invention is achieved through the following technical solutions:
[0009] On the one hand, the present invention provides a mixed high corrosion resistant FeSiCr electromagnetic wave absorber, which is a mixed absorber formed by uniformly distributing flaky FeSiCr powder and spherical FeSiCr powder; in terms of mass percentage, the mixed high corrosion resistant FeSiCr electromagnetic wave absorber includes 5 to 15 wt% of flaky FeSiCr powder, and the rest is spherical FeSiCr powder.
[0010] Furthermore, the chemical composition and content of the flaky FeSiCr powder are: 7-9wt% Si, 2-4wt% Cr, and the rest Fe;
[0011] The chemical composition and content of the spherical FeSiCr powder are: Si is 7-9wt%, Cr is 2-4wt%, and the rest is Fe.
[0012] Furthermore, the particle size of the spherical FeSiCr powder is 2 to 5 μm.
[0013] Furthermore, the particle size of the flaky FeSiCr powder is less than 10 μm, and the long diameter is greater than 20 μm.
[0014] Further preferably, the chemical composition and content of the flaky FeSiCr powder and the spherical FeSiCr powder are: 8wt% Si, 2.5wt% Cr, and the rest Fe.
[0015] The present invention also provides a method for preparing a mixed high corrosion-resistant FeSiCr electromagnetic wave absorber, comprising the following steps:
[0016] A. Preparation of spherical FeSiCr powder:
[0017] a1. According to 7-9wt% Si, 2-4wt% Cr and the rest Fe, weigh iron rods, silicon particles and chromium ingots as raw materials;
[0018] a2. Melt the iron rod, silicon particles and chromium ingots in a vacuum induction melting furnace to make alloy. After the molten metal is melted for 2-3 minutes, powder is made by water mist or gas mist method.
[0019] a3. The powder obtained in step a2 is sieved to obtain spherical FeSiCr powder with a particle size of 2 to 5 μm and fine particles with a particle size of 5 to 10 μm;
[0020] B. Preparation of flake powder:
[0021] b1. Use zirconium oxide balls to add fine particles of 5-10 μm into a ball mill at a material-ball ratio of 1:20, and add special ball milling agent. The speed is 400 r / min and wet milling is performed for 5 hours to obtain flaky powder with a particle size of <10 μm.
[0022] b2, drying the flaky powder obtained in b1 at 60° C. to obtain dried flaky powder;
[0023] C. Powder stress relief annealing treatment:
[0024] The dried flaky powder was placed in a vacuum tube furnace, nitrogen was introduced for protection, and the temperature was kept at 700°C for 3 hours to obtain flaky FeSiCr powder;
[0025] D. Preparation of mixed powder:
[0026] The two powders, flaky FeSiCr powder and spherical FeSiCr powder, are ball-milled and mixed in a ratio of 5-15wt% of flaky FeSiCr powder and the rest of spherical FeSiCr powder to obtain a mixed FeSiCr powder, that is, a mixed high corrosion-resistant FeSiCr electromagnetic wave absorber.
[0027] Furthermore, in the step D, the ball milling speed is 200 r / min, and the ball milling time is 10 min. The spherical FeSiCr powder and the flaky FeSiCr powder can be evenly distributed, and the particle size and shape of the spherical FeSiCr powder and the flaky FeSiCr powder will not change.
[0028] Furthermore, in step A, the purity of the iron rod, silicon particles and chromium ingots is greater than 99.9%.
[0029] Furthermore, in step A, the alloy is melted in a vacuum induction melting furnace, and the vacuum before melting is less than 0.1 Pa, and is controlled at about 1 Pa during melting.
[0030] Furthermore, the zirconia ball is made of and Three kinds of zirconia balls are mixed, and and The mass ratio of the three types of zirconia balls is 8:3:1.
[0031] It should be noted that the role of stress annealing is to increase the magnetic permeability of the absorbent, improve the electrochemical uniformity of the material interface, and improve corrosion resistance.
[0032] It should be noted that the morphological characteristics of the absorbent will have a great influence on the magnetic permeability. The flake shape is beneficial to low frequency, and the spherical shape is beneficial to high frequency. The particle size of the absorbent will affect the peak value of the magnetic permeability. Therefore, in the prior art, when designing the absorbent component, in order to ensure that the absorbent has good magnetic permeability, the particle size of the absorbent is controlled at about 10μm. The present solution innovatively discovered that by preparing the FeSiCr powder into spherical FeSiCr powder with a particle size of 2 to 5μm, and mixing it with flaky FeSiCr powder with a particle size of <10μm by ball milling, the obtained mixed absorbent can ensure the high magnetic permeability in the microwave high frequency band, and at the same time has outstanding corrosion resistance.
[0033] In the present invention, a certain amount of Cr is added to the FeSi alloy, which can appropriately optimize the corrosion resistance of the absorbent, and the spherical shape has higher corrosion resistance than the flake shape. After the spherical FeSiCr powder, which is slightly smaller than the flake powder, is evenly distributed with the spherical FeSiCr powder, a spatial distribution that fills each other is formed in three-dimensional space, and a spatial structure that is more rigorous than the flake FeSiCr powder and more dispersed than the spherical FeSiCr powder is formed.
[0034] The beneficial effects of the present invention are as follows: 1) In this scheme, 2-5 μm spherical FeSiCr powder and 5-10 μm fine particles are prepared by atomization method, and the fine particles are ball-milled to obtain flaky powder with a particle size of <10 μm; the flaky powder is stress-relieved and annealed, and then ball-milled and mixed with 2-5 μm spherical FeSiCr powder to obtain a mixed high-corrosion-resistant FeSiCr electromagnetic wave absorber, and the flaky FeSiCr powder accounts for 5-15 wt% in the mixed absorber; the mixed absorber prepared by this scheme has the characteristics of high magnetic permeability and strong corrosion resistance in the microwave high frequency band, and the tap density can be adjusted by the ratio of flaky powder to spherical powder, and can be applied to coating materials with high requirements for corrosion resistance and electromagnetic wave absorption performance in marine environments;
[0035] 2) The hybrid high corrosion-resistant FeSiCr electromagnetic wave absorber of the present invention does not require special preparation equipment, but only requires traditional atomization powder making equipment, a ball mill, and a tubular annealing furnace; the device is simple, the operation is simple, the cost is low, and it is easy to realize industrialization;
[0036] 3) The present invention adopts zirconium oxide grinding balls and controls the ball milling time to obtain ideal flaky FeSiCr powder; by controlling the ratio of flaky FeSiCr powder to spherical FeSiCr powder, the peak value and density of the magnetic permeability of the electromagnetic wave absorber can be adjusted simultaneously, thereby meeting the use requirements of a specific frequency band. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 is a SEM image of the mixed high corrosion-resistant FeSiCr electromagnetic wave absorber prepared in Example 1 of the present invention;
[0038] Figure 2 is a graph showing the relationship between dielectric constant and frequency of the present invention;
[0039] Figure 3 It is the relationship diagram between magnetic permeability and frequency of the present invention;
[0040] Figure 4 It is a Tafel picture. DETAILED DESCRIPTION
[0041] The technical solution of the present invention is further described in detail below in conjunction with the accompanying drawings, but the protection scope of the present invention is not limited to the following.
[0042] Example 1
[0043] 1) Preparation of spherical powder:
[0044] Firstly, high-purity iron rods, silicon particles and chromium ingots with purities greater than 99.9% are used to prepare raw materials; silicon and chromium are respectively 8wt% Si and 2.5wt% Cr, and the rest is Fe;
[0045] Then the prepared raw materials are melted into alloy in a vacuum induction melting furnace. The vacuum before melting is less than 0.1Pa and is controlled at about 1Pa during melting to ensure that the vacuum requirements for raw materials during melting are met. After the melt is melted for 2-3 minutes, water mist method powdering is carried out.
[0046] The powder is then sieved to obtain spherical FeSiCr powder with a particle size of 2 to 5 μm and fine particles with a particle size of 5 to 10 μm;
[0047] 2) Preparation of flake powder
[0048] use and Three kinds of zirconium oxide balls, add 5-10μm fine particles into the ball mill at a material-ball ratio of 1:20, add appropriate amount of special ball milling agent for wet grinding, the speed is 400r / min, wet grinding for 5h, obtain flaky powder with a particle size of <10μm, and then dry it at 60℃ to obtain dried flaky powder;
[0049] 3) Powder stress relief annealing treatment: The dried flaky powder obtained above is placed in a vacuum tube furnace, nitrogen is introduced for protection, and the temperature is kept at 700° C. for 3 hours to obtain flaky FeSiCr powder with a particle size of <10 μm and an aspect ratio of greater than 20;
[0050] 4) Preparation of mixed powder: Flake FeSiCr powder and spherical FeSiCr powder are ball-milled and mixed, wherein the flake FeSiCr powder accounts for 5wt% and the rest is spherical FeSiCr powder; the ball milling speed is 200r / m, and after ball milling for 10min, a mixed high corrosion-resistant FeSiCr electromagnetic wave absorber is obtained;
[0051] 5) Pressing ring test: The above-mentioned mixed high corrosion-resistant FeSiCr electromagnetic wave absorber and paraffin were mixed in a ratio of 6:1, pressed into a Φ7mm×Φ3mm×3mm ring sample, and the electromagnetic parameters of the mixed high corrosion-resistant FeSiCr electromagnetic wave absorber were measured, and the maximum value of the imaginary part of the magnetic permeability was 2.05, and the frequency was 2.6GHz;
[0052] 6) Corrosion resistance test: The above-mentioned mixed high corrosion-resistant FeSiCr electromagnetic wave absorber was mixed with carbon black and polyvinylidene fluoride in a ratio of 8:1:1, and an appropriate amount of N-methylpyrrolidone was added. The mixture was stirred for 20 minutes, vacuumed, and dried at 50°C to form a thin sheet. The open circuit and Tafel diagram were tested using an electrochemical workstation, and the corrosion rate was measured to be 0.00446 mm / year, and the corrosion resistance grade was 2.
[0053] In this embodiment, in step 2), and The mass ratio of the three zirconia balls is 8:3:1.
[0054] Example 2
[0055] The only difference between this embodiment and embodiment 1 is that: in step 2), the flaky FeSiCr powder accounts for 10wt% and the rest is spherical FeSiCr powder; the final test shows that the maximum value of the imaginary part of the magnetic permeability is 2.06, the frequency is 2.9GHz; its corrosion rate is 0.00462mm / year, and the corrosion resistance level is level 2.
[0056] Example 3
[0057] The steps of this embodiment are consistent with those of embodiment 1, and the only difference between this embodiment and embodiment 1 is that Cr is changed to 3wt% in step 1). Finally, the maximum value of the imaginary part of the magnetic permeability is 2.14, the frequency is 3.0GHz, the corrosion rate is 0.00437mm / year, and the corrosion resistance grade is 2.
[0058] From the comparison between Example 1 and Example 3, it can be seen that as the Cr content increases, the peak value, frequency and corrosion resistance of the imaginary part of the magnetic permeability increase.
[0059] From the comparison between Example 1 and Example 2, it can be seen that as the proportion of flaky FeSiCr powder increases, the imaginary part of the magnetic permeability increases slightly, but the frequency at the peak moves to the high frequency, and the corrosion resistance decreases; thus, by controlling the ratio of flaky FeSiCr powder to spherical FeSiCr powder, this scheme can simultaneously adjust the peak value and density of the magnetic permeability of the electromagnetic wave absorber, thereby meeting the use requirements of a specific frequency band.
[0060] The above is only a preferred embodiment of the present invention. It should be understood that the present invention is not limited to the form disclosed herein, and should not be regarded as excluding other embodiments, but can be used in various other combinations, modifications and environments, and can be modified within the scope of the concept described herein through the above teachings or the technology or knowledge of the relevant field. The changes and modifications made by those skilled in the art shall not deviate from the spirit and scope of the present invention, and shall be within the scope of protection of the claims attached to the present invention.
Claims
1. A mixed high corrosion resistant FeSiCr electromagnetic wave absorber, characterized in that: The mixed high corrosion-resistant FeSiCr electromagnetic wave absorber is a mixed absorber in which both flaky FeSiCr powder and spherical FeSiCr powder are evenly distributed; In terms of mass percentage, the mixed high corrosion-resistant FeSiCr electromagnetic wave absorber includes 5-15wt% of flaky FeSiCr powder and the rest of spherical FeSiCr powder; The chemical composition and content of the flaky FeSiCr powder are: Si is 7-9wt%, Cr is 2-4wt%, and the rest is Fe; The chemical composition and content of the spherical FeSiCr powder are: Si is 7-9wt%, Cr is 2-4wt%, and the rest is Fe; The particle size of the spherical FeSiCr powder is 2-5 μm; The particle size of the flaky FeSiCr powder is less than 10 μm, and the long diameter is greater than 20 μm.
2. The hybrid high corrosion resistant FeSiCr electromagnetic wave absorber according to claim 1, characterized in that: The chemical composition and content of the flaky FeSiCr powder and the spherical FeSiCr powder are: 8wt% Si, 2.5wt% Cr, and the rest Fe.
3. A method for preparing the hybrid high corrosion resistant FeSiCr electromagnetic wave absorber according to any one of claims 1 to 2, characterized in that: The following steps are involved: A. Preparation of spherical FeSiCr powder: a1. Assuming Si is 7-9wt%, Cr is 2-4wt%, and the rest is Fe, weigh iron rods, silicon particles and chromium ingots as raw materials; a2. Melt the iron rod, silicon particles and chromium ingots in a vacuum induction melting furnace to make alloy. After the molten metal is melted for 2-3 minutes, powder is made by water mist or gas mist method. a3. The powder obtained in step a2 is sieved to obtain spherical FeSiCr powder with a particle size of 2-5 μm and fine particles with a particle size of 5-10 μm; B. Preparation of flake powder: b1. Use zirconium oxide balls to add 5~10μm fine particles into a ball mill at a material-ball ratio of 1:20, and add special ball milling agent. The speed is 400r / min and wet milling is performed for 5h to obtain flaky powder with a particle size of <10μm. b2, drying the flaky powder obtained in b1 at 60° C. to obtain dried flaky powder; C. Powder stress relief annealing treatment: The dried flaky powder was placed in a vacuum tube furnace, nitrogen was introduced for protection, and the temperature was kept at 700°C for 3 hours to obtain flaky FeSiCr powder; D. Preparation of mixed powder: The two powders, flaky FeSiCr powder and spherical FeSiCr powder, are ball-milled and mixed in a ratio of 5-15wt% of the flaky FeSiCr powder and the rest of the spherical FeSiCr powder to obtain a mixed FeSiCr powder, that is, a mixed high corrosion-resistant FeSiCr electromagnetic wave absorber.
4. A method for preparing a hybrid high corrosion resistant FeSiCr electromagnetic wave absorber according to claim 3, characterized in that: In the step D, the rotation speed of the ball milling is 200 r / min, and the ball milling time is 10 min.
5. A method for preparing a hybrid high corrosion resistant FeSiCr electromagnetic wave absorber according to claim 4, characterized in that: In the step A, the purity of the iron rod, silicon particles and chromium ingots is greater than 99.9%.
6. A method for preparing a hybrid high corrosion resistant FeSiCr electromagnetic wave absorber according to claim 5, characterized in that: In step A, the alloy is melted in a vacuum induction melting furnace. The vacuum before melting is less than 0.1 Pa and is controlled at about 1 Pa during melting.
7. A method for preparing a hybrid high corrosion resistant FeSiCr electromagnetic wave absorber according to claim 6, characterized in that: The zirconia balls are a mixture of three types of zirconia balls of φ2.5, φ5 and φ10, and the mass ratio of the three types of zirconia balls of φ2.5, φ5 and φ10 is 8:3:1.
Citation Information
Patent Citations
Carbon-coated FeSiCr magnetic nano wave absorbing material and preparation method thereof
CN109054740A
Iron-silicon-chromium magnetically soft alloy powder and preparation method thereof
CN111575603A
Preparation method for wave absorbing material with high magnetic conductivity
CN107507689A
Carbonyl iron powder wave-absorbing material and preparation method thereof
CN113773610A